Prevalence of Provocative Seizures in Persons with Epilepsy: A Longitudinal Study at Khon Kaen University Hospital, Thailand - Nutthaya Vongkasamchai; Sunee Lertsinudom; Acharawan Topark-Ngarm; Udomlack Peansukwech; Kittisak Sawanyawisuth; Somsak Tiamkao; Integrated Epilepsy Research Group (Neurology Research International)
Background and Objective. Provocative factors are one causative factor of seizure attacks in persons with epilepsy (PWE). There are limited data of prevalence and major provocative factors in Asian populations. Methods. This study was performed at the Epilepsy Clinic, Khon Kaen University Hospital. The patients who aged 15 years or over, who had been treated at least 3 months with at least one antiepileptic drug, and who were followed up for at least one year were included. Data of seizure control and triggers were collected retrospectively from medical records. Data analysis was performed to identify independent provocative factors. Results. A total of 382 PWE met the study criteria. The mean age was 40.4±0.8 years. Approximately 44% of the patients had at least one provocative factor. By multivariate analysis, the independent provocative factors with the first three highest adjusted odds ratios were sleep deprivation (adjusted OR=8.64, 95% CI 3.73–19.99), alcohol consumption (adjusted OR=6.76, 95% CI 1.44–31.78), and feeling stressful (adjusted OR=2.97, 95% CI 1.29–6.86). Conclusion. Almost half of seizure attacks may be caused by provocative factors in Thai PWEs and some factors may be preventable. Avoidance of these factors should be emphasized to epilepsy patients for improving clinical outcomes and quality of life.